2020
DOI: 10.18332/tpc/115031
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing cigarette smoking among police and costs of an officer smoking in the workplace at Nsambya Barracks, Uganda

Abstract: INTRODUCTION Studies in several countries indicate that being a police officer is a risk factor for tobacco use. Currently, no such studies have been performed among police officers in Uganda, or in Africa generally. The aim of this study is to assess prevalence and costs of smoking among Ugandan police officers. METHODS A multistage survey model was employed to sample police officers (n=349) that included an observational cross-sectional survey and an annual costanalysis approach. The study setting was confin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 14 publications
0
5
0
4
Order By: Relevance
“…Similarly, traffic police officers with alcohol consumption habits had higher odds of having anxiety symptoms. This finding is supported by various studies where dependence on smoking, alcohol and substance use has been mentioned among the police due to their lifestyles and working environment 38–40. Previous studies had shown that lack of resources, poor infrastructure and a high number of vehicles contributed to poor mental health in traffic police officers.…”
Section: Discussionmentioning
confidence: 56%
“…Similarly, traffic police officers with alcohol consumption habits had higher odds of having anxiety symptoms. This finding is supported by various studies where dependence on smoking, alcohol and substance use has been mentioned among the police due to their lifestyles and working environment 38–40. Previous studies had shown that lack of resources, poor infrastructure and a high number of vehicles contributed to poor mental health in traffic police officers.…”
Section: Discussionmentioning
confidence: 56%
“…Másfelől a rendőri szolgálat természetéből fakadóan olyan környezetet teremt, amely motiválhatja a dohányzást. Egyes vizsgálatok szerint ugyanis a rendőrök körében akár 4,8-szor magasabb lehet a dohányzók aránya (25,5% vs. 5,3%) az átlag populációhoz képest (Basaza et al, 2020).…”
Section: Következtetésekunclassified
“…Korábbi vizsgálatok legalábbis azt jelzik, hogy a rendőrség munkatársai között például magasabb a dohányzás előfordulása a civilekhez képest (Smith et al 2005). A rendőrök körében akár 4,8-szor magasabb lehet a dohányzók aránya (25,5% vs. 5,3%) az átlag populációhoz képest (Basaza et al 2020). Jankowski és munkatársai (Jankowski et al 2021) lengyel rendőrökön végzett vizsgálata szintén azt mutatta, hogy az átlag népességhez viszonyítva a rendőrök között magasabb a dohányzás kipróbálásának prevalenciája (52% vs. 54,6%), míg a napi dohányosok aránya a civilekhez mérten alacsonyabb volt az egyenruhások között (21% vs. 19,5%).…”
Section: Bevezetésunclassified
“…Egy, az ugandai rendőrök körében végzett kutatás eredményei szerint a dohányzás éves költsége a termelékenység csökkenése miatt akár az 5,521 millió USD-t is elérheti éves szinten, a többlet egészségügyi költségek pedig 57,316 millió USD-t tesznek ki. Ezek a költségek a 2018-2019-es pénzügyi évben az ugandai állami rendőrség költségvetésének 45,1%-át tették ki (Basaza et al 2020).…”
Section: Megbeszélés Következtetésekunclassified
See 1 more Smart Citation